2019 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--32983
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Comics Into Engineering Education To Promote Student Interest, Confidence, and Understanding

Abstract: The use of comics as an educational teaching tool is a practice that has existed for several decades but only recently begun to be utilized in STEM fields. The dramatic expansion in STEM comics through independent artists, book series, and video animation has illustrated the opportunity for the integration of art into STEM to improve educational approaches. Despite a continued general perception that comics are 'childish', comics have a unique and demonstrated potential for improving student enthusiasm, confid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…As this pedagogical approach emerged and has been refined over the last two years, our next step is to develop a formal research program to assess the efficacy and impact of this approach to engineering leadership education. We anticipate that we will have favourable results based on our experiences using this approach in the classroom and given prior research that indicated enhanced learning outcomes from the use of regular comics for teaching technical subject matter to engineering students [12].…”
Section: Vivid Storytellingmentioning
confidence: 99%
See 2 more Smart Citations
“…As this pedagogical approach emerged and has been refined over the last two years, our next step is to develop a formal research program to assess the efficacy and impact of this approach to engineering leadership education. We anticipate that we will have favourable results based on our experiences using this approach in the classroom and given prior research that indicated enhanced learning outcomes from the use of regular comics for teaching technical subject matter to engineering students [12].…”
Section: Vivid Storytellingmentioning
confidence: 99%
“…An added benefit to VIVID Storytelling using educational comics is that it circumvents the biases hidden within the complex language of academia [1], which is often used as the basis from which leadership material is taught to engineering students. In fact, comics have been found to even enhance student interest, comprehension, and confidence in technical engineering material [12].…”
Section: Vivid Storytellingmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors had previously developed a series of comics for use in chemical engineering courses at the undergraduate level and evaluated their initial impact on student interest, confidence, and understanding. [25][26] These comics included discussion of purge and recycle streams, 27 the first law of thermodynamics, 28 assumptions, 29 heat exchangers, 30 and other chemical engineering concepts. In general, the comics were shown to have a significant effect on students' self-reported interest in the subject matter and confidence in being able to address problems or applications involving the concepts that the comics addressed.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the comics were shown to have a significant effect on students' self-reported interest in the subject matter and confidence in being able to address problems or applications involving the concepts that the comics addressed. [25][26] The impact of understanding was less clear, depending on how the comics were implemented. Small improvement was observed in student performance on exams and lab reports for some courses, while other results were mixed if the instructor was not directly supportive of the comics being introduced.…”
Section: Introductionmentioning
confidence: 99%